Cardiometabolic and Kidney Protection in Kidney Transplant Recipients With Diabetes: Mechanisms, Clinical Applications, and Summary of Clinical Trials. Issue 4 (11th August 2021) - Sridhar, Vikas S.; Ambinathan, Jaya Prakash N.; Gillard, Pieter; Mathieu, Chantal; Cherney, David Z.I.; Lytvyn, Yuliya; Singh, Sunita K.
Abstract : Abstract. Kidney transplantation is the therapy of choice for patients with end-stage renal disease. Preexisting diabetes is highly prevalent in kidney transplant recipients (KTR), and the development of posttransplant diabetes is common because of a number of transplant-specific risk factors such as the use of diabetogenic immunosuppressive medications and posttransplant weight gain. The presence of pretransplant and posttransplant diabetes in KTR significantly and variably affect the risk of graft failure, cardiovascular disease (CVD), and death. Among the many available therapies for diabetes, there are little data to determine the glucose-lowering agent(s) of choice in KTR. Furthermore, despite the high burden of graft loss and CVD among KTR with diabetes, evidence for strategies offering cardiovascular and kidney protection is lacking. Recent accumulating evidence convincingly shows glucose-independent cardiorenal protective effects in non-KTR with glucose-lowering agents, such as sodium–glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists. Therefore, our aim was to review cardiorenal protective strategies, including the evidence, mechanisms, and rationale for the use of these glucose-lowering agents in KTR with diabetes.